Interrupting Violence: How the CeaseFire Program Prevents Imminent Gun Violence through Conflict Mediation - Whitehill, Jennifer M. (Springer US, 2013)
Cities are increasingly adopting CeaseFire, an evidence-based public health program that uses specialized outreach workers, called violence interrupters (VIs), to mediate potentially violent conflicts before they lead to a shooting. Prior research has linked conflict mediation with program-related reductions in homicides, but the specific conflict mediation practices used by effective programs to prevent imminent gun violence have not been identified. We conducted case studies of CeaseFire programs in two inner cities using qualitative data from focus groups with 24 VIs and interviews with eight program managers. Study sites were purposively sampled to represent programs with more than 1 year of implementation and evidence of program effectiveness. Staff with more than 6 months of job experience were recruited for participation. Successful mediation efforts were built on trust and respect between VIs and the community, especially high-risk individuals. In conflict mediation, immediate priorities included separating the potential shooter from the intended victim and from peers who may encourage violence, followed by persuading the parties to resolve the conflict peacefully. Tactics for brokering peace included arranging the return of stolen property and emphasizing negative consequences of violence such as jail, death, or increased police attention. Utilizing these approaches, VIs are capable of preventing gun violence and interrupting cycles of retaliation.